The Effectiveness of the Use of Computer Programs in the Organization of Practical Training in Astronomy. - Z. A. Avezmuratova (Zien Journals, 2022)
In this paper presents the observations at the practical lessons, particularly on the Internet and the Stellarium programs, including visual observation of the planet Mars and its surface movement. This method are useful for a teachers, students and interesting persons.
Keywords: Ecliptic; Jupiter; Polaris; Sirius